El Corazón bajo la Cama. Arteterapia con una Niña Superviviente de Abusos - LLANOS ALONSO, María (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2010)
How to use art therapy with trauma survivors is illustrated through the case of a child survivor from sexual abuse. Some theories about trauma are explained, as well as how important it is with these patients to maintain the setting, to nurture the therapeutic bond and to choose carefully the art materials.
Keywords: Art therapy; Child; Sexual abuse; Trauma; Art materials